The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1073/pnas.1202641109
|View full text |Cite|
|
Sign up to set email alerts
|

CCAAT/enhancer-binding protein δ facilitates bacterial dissemination during pneumococcal pneumonia in a platelet-activating factor receptor-dependent manner

Abstract: The authors note that on page 13064, right column, first full paragraph, lines 4-7, "Some of the climatic events linked to such concerns are the severe droughts experienced by the Amazon basin in 2005 and 2010, which reportedly reduced tropical forest NPP by 1.6 to 2.2 PgC/y and increased tree mortality (50, 51)" should instead appear as "Some of the climatic events linked to such concerns are the severe droughts experienced by the Amazon basin in 2005 and 2010, which reportedly reduced tropical forest NPP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…Pictures of collagen staining were taken to cover the entirety of all sections. Colour intensity of stained areas was analysed semi-quantitatively with ImageJ and expressed as percentage of the surface area essentially as described before 24 25. For details, see the online supplementary method section.…”
Section: Methodsmentioning
confidence: 99%
“…Pictures of collagen staining were taken to cover the entirety of all sections. Colour intensity of stained areas was analysed semi-quantitatively with ImageJ and expressed as percentage of the surface area essentially as described before 24 25. For details, see the online supplementary method section.…”
Section: Methodsmentioning
confidence: 99%
“…This corroborates other studies that showed an increase of PAFR in the onset of different diseases, like systemic infection, necrotizing enterocolitis, graft-vs-host disease and peripheral nerve injury. [23][24][25][26] As expected, initially, the infiltrating immune cells must be responsible for PAFR expression upregulation, and at later time points the renal cells are also responsible for the maintenance of higher PAFR expression. PAF and a wide range of oxidatively modified phospholipids are recognized by PAFR that is constitutively expressed by cells participating in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…(immuno)histochemistry Histological examination was performed essentially as previously described (29,30). Briefly, the excised tumor was fixed in formalin, embedded in paraffin and 4 μm thick slides were subsequently deparaffinized, rehydrated and washed in deionized water.…”
Section: Orthotopic Pancreatic Cancer Modelmentioning
confidence: 99%